Inappropriate therapy and shock rates between the subcutaneous and transvenous implantable cardiac defibrillator: a secondary analysis of the PRAETORIAN trial - Olde Nordkamp, Louise R.A; Pepplinkhuizen, Shari; Ghani, Abdul; Boersma, Lucas V.A.; Kuschyk, Jürgen; El-Chami, Mikhael F.; Behr, Elijah R.; Brouwer, Tom F.; Kääb, Stefan; Mittal, Suneet; Quast, Anne-Floor B.E.; van der Stuijt, Willeke; et al. (Circulation. Arrhythmia and electrophysiology, 2024)
BACKGROUND: - Inappropriate therapy (IAT) is an undesirable side effect of implantable cardiac defibrillator (ICD) therapy. Early studies with the subcutaneous ICD (S-ICD) showed relatively high inappropriate shock (IAS) rates. The PRAETORIAN (Prospective Randomized Comparison of Subcutaneous and Transvenous Implantable Cardioverter Defibrillator Therapy) trial demonstrated that the S-ICD is noninferior to the transvenous ICD (TV-ICD) with regard to the combined end point of IAS and complications. This secondary analyses evaluates all IAT in the PRAETORIAN trial. - METHODS: - This international, multicenter trial randomized 849 patients with an indication for ICD therapy between S-ICD (n=426) and TV-ICD therapy (n=423). ICD programming was mandated by protocol. All analysis were performed in the modified intention-to-treat population. - RESULTS: - In both groups 42 patients experienced IAT (48-month Kaplan-Meier estimated cumulative incidence, 9.9% and 10.1%, respectively; hazard ratio (HR), 0.99 [95% CI, 0.65-1.52]; P=0.97). There was no significant difference in patients experiencing IAS between both groups (P=0.14). In the S-ICD group, 81 IAT episodes with 124 IAS and 1 inappropriate antitachycardia pacing occurred versus 89 IAT episodes with 130 IAS and 124 inappropriate antitachycardia pacing in the TV-ICD group. IAT episodes were most frequently caused by supraventricular tachycardias in the TV-ICD group (n=83/89) versus cardiac oversensing in the S-ICD group (n=40/81). In the TV-ICD group, a baseline heart rate >80 bpm (HR, 1.99 [95% CI, 1.05-3.76]; P=0.03), a history of atrial fibrillation (HR, 2.66 [95% CI, 1.41-5.02]; P=0.003), and smoking (HR, 2.46 [95% CI, 1.31-4.09]; P=0.005) were independent predictors for IAT. A QRS duration >120 ms was an independent predictor for IAT caused by cardiac oversensing in the S-ICD group (HR, 3.13 [95% CI, 1.34-7.31]; P=0.008). Post-IAS interventions significantly reduced IAS recurrence in both groups (P=0.046). - CONCLUSIONS: - There was no significant difference in IAT and IAS rates between the S-ICD and TV-ICD in a conventional ICD population, but causes and predictors for IAT differed between the devices. After the first IAS, an intervention significantly reduced the recurrence rate of IAS. - REGISTRATION: - URL: https://www.clinicaltrials.gov; Unique identifier: NCT01296022.
Ursprünglich veröffentlicht: 3. Dezember 2024
Gesehen am 15.04.2025